Notions of Ishtiqaq and Sunaiyyah in Arabic - Kahayev, Amir (Scholarya Demo Journal of Ruby, 2019)
The article discusses the notion of ishtiqaq (derivation), its types and usageto express different contents. It introduces various explanations of the termishtiqaq al-akbar and states that its introduction as a new term with differentmeanings is inappropriate. It discusses Jinni, Abdussalam Mahammad Harunand Abdulla Emin’s views on ishtiqaq al-akbar. The article sheds light on howIbn Jinni finds common meaning in ishtiqaq al-akbar and ibn Faris in ishtiqaqal-saghir and how classical and modern writers distinguish and explain ishtiqaqtypes. It also studies the notion of sunaiyyah (bilateralism) and concludes thatit is possible to understand the interpretation of it through the works of thescholars such as Khalil ibn Ahmad, Ibn Jinni and Faris. In his book Mu'jammaqayis al-lughah, Ibn Faris provides some examples that support this idea.According to the author, the meaning do not change if the third letter is changedin a word. This proves that Ibn Faris shared the same thoughts with the scholarswho suggested that the word roots in Arabic consist of two letters. The articlethen discussses the origin of EÖ:and material meanings. According to ibnFaris, material meaning derived from EÖ:meaning which appeared first.Some contemporary writers oppose this idea and consider that materialmeaning originated first.